Impact of ablation on regional strain from 4D computed tomography in the left atrium - Mehringer, Noah; Severance, Lauren; Park, Aaron; Ho, Gordon; McVeigh, Elliot (Journal of interventional cardiac electrophysiology, 2025)
Ablation for atrial fibrillation targets an arrhythmogenic substrate in the left atrium (LA) myocardium with therapeutic energy, resulting in a scar tissue. Although a global LA function typically improves after ablation, the injured tissue is stiffer and non-contractile. The local functional impact of ablation has not been thoroughly investigated. This study retrospectively analyzed the LA mechanics of 15 subjects who received a four-dimensional computed tomography (4DCT) scan pre- and post-ablation for atrial fibrillation. LA volumes were automatically segmented at every frame by a trained neural network and converted into surface meshes. A local endocardial strain was computed at a resolution of 2 mm from the deforming meshes. The LA endocardial surface was automatically divided into five walls and further into 24 sub-segments using the left atrial positioning system. Intraoperative notes gathered during the ablation procedure informed which regions received ablative treatment. In an average of 18 months after ablation, the strain is decreased by 16.3% in the septal wall and by 18.3% in the posterior wall. In subjects who were imaged in sinus rhythm both before and after the procedure, the effect of ablation reduced the regional strain by 15.3% (p = 0.012). Post-ablation strain maps demonstrated spatial patterns of reduced strain which matched the ablation pattern. This study demonstrates the capability of 4DCT to capture high-resolution changes in the left atrial strain in response to tissue damage and explores the quantification of a regionally reduced LA function from the scar tissue.